Mañé-Estrada, A., Thieux, L. y M. Hernando de Larramendi (2019): Argelia en Transición hacia una Segunda República, Barcelona, Icaria, 135 pp - Szmolka Vida, Inmaculada (Política y Sociedad, 2020)
No procede